Teschovirus and other swine and human enteric viruses in Brazilian watersheds impacted by swine husbandry - Souza, F. G. (Braz J Microbiol, 2019)
Several emerging viral agents related to gastroenteritis are distributed in human and animal populations and may contaminate the environment due to anthropic activities. The objective of this study was to analyze the seasonal contamination by enteric virus and coliforms in water from streams in the Vale do Taquari, draining a large number of pig farms. Microbiological contamination was evidenced by the detection of total and thermotolerant coliforms, reaching their peak in December. Hepatitis E virus (HEV), Enterovirus-G (EV-G) genome, and Sapelovirus-A (SV-A) genome were not detected. On the other hand, Rotavirus (RV) was detected in 3% (1/32) of the samples, whereas Teschovirus-A (PTV) was detected in 6% (2/32). This is the first detection of PTV in environmental samples in Brazil, pointing that the virus is being shedded from swine herds to watersheds. Human mastadenovirus (HAdV) was the most frequent detected viral agent in 9.3% (3/32) with values of 2.54 × 10(5), 7.13 × 10(4), and 3.09 × 10(5) genome copies/liter (gc/L). The circulation of coliforms and viral pathogens is noticeable due to anthropic activities and to the management of animal waste from the pig farming. In this way, enteric viruses can assist in monitoring the quality of watersheds and in tracking sources of contamination.